Belajar Satuan Ukur Melalui Motif Tenun Sumba Pendekatan Matematika Kontekstual Di SDK Marsudirini Tambolaka - Setiawi, Agustina Purnami (Adi Widya: Jurnal Pendidikan Dasar, 2024)
Contextual-based mathematics learning is an innovative approach to improving students' understanding, particularly in strengthening critical thinking skills. One implementation of this approach is through the exploration of Sumba woven motifs, which are rich in geometric patterns, to teach measurement concepts at the elementary school level. Sumba woven motifs are utilized as concrete learning media to help students grasp the measurement of length, area, and scale. This approach enables students to connect abstract mathematical concepts with relevant everyday experiences, thereby increasing their interest in learning. Research findings indicate a significant improvement in students' average scores, from 65 in the pretest to 85 in the posttest after applying this method. Moreover, this approach enhances students’ appreciation of local culture, supports cultural preservation, and fosters pride in their regional identity. The primary challenges in implementing this method include a lack of standardized teaching materials and limited time within the formal curriculum. Therefore, teacher training and collaboration between schools and local communities are necessary to enrich teaching resources. Such culture-based approaches not only train students' critical thinking abilities but also bridge formal education with cultural preservation, making it a strategic solution for creating relevant and meaningful learning experiences.